Defining immune reset: achieving sustained remission in autoimmune diseases - Junt, Tobias; Calzascia, Thomas; Traggiai, Elisabetta; da Costa, André Nogueira; Gergely, Peter; Schett, Georg; Dörner, Thomas; Siegel, Richard M. (Nature Reviews Immunology, 2025)
Personalized cell therapies for autoimmune diseases — such as autologous haematopoietic stem cell transplantation and chimeric antigen receptor-expressing T cells — have the potential to achieve sustained remission in patients with certain autoimmune diseases. The effective elimination of pathogenic lymphocytes and their subsequent repopulation with naive cells has been termed ‘immune reset’. In this Perspective, we trace the origins of the immune reset concept and its clinical, cellular and molecular definitions, and we review current attempts to identify biomarkers for long-term clinical remission in autoimmune diseases. Emerging data from clinical trials support the concept that higher probabilities of long-term remission can be achieved with therapies that can more deeply and broadly deplete B cells than the anti-CD20 antibody rituximab. A better understanding of the cellular and molecular basis for immune reset and the biomarkers associated with this state should accelerate progress towards the goal of restoring a non-autoimmune state and sustaining remission, while reducing the need for chronic immunosuppression.
CRIS-Team Scopus Importer:2025-03-21